Nonaqueous electrolyte and lithium secondary battery containing same

By adjusting the freedom of ethanol diacid and using a combination of non-solvents and lithium salts, a non-aqueous electrolyte that can inhibit the decomposition of ethanol diacid was prepared, which solved the gas generation problem caused by decomposition of ethanol diacid in the prior art, and achieved the safety and volume stability of lithium secondary batteries.

JP2025510855AActive Publication Date: 2025-04-15LG ENERGY SOLUTION LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024556760
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-30
Filing Date
2023-03-30
Publication Date
2025-04-15
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The decomposition of ethanol diacid in existing non-aqueous electrolytes leads to gas generation, affecting the safety and volume stability of lithium secondary batteries.

Method used

By adjusting the degree of freedom of ethanol diacid in the electrolyte to ensure that it is within the range of 30% or less, a non-aqueous electrolyte that does not participate in the decomposition of lithium ion is prepared to effectively inhibit the decomposition of ethanol diacid.

Benefits of technology

It significantly reduces the amount of gas generated during battery operation, improves the safety and volume stability of lithium secondary batteries, and maintains the high energy density and good electrochemical properties of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025510855000001_ABST
    Figure 2025510855000001_ABST
Patent Text Reader

Abstract

The present invention relates to a non-aqueous electrolyte comprising an organic solvent containing ethylene carbonate, a non-solvent, and a lithium salt, in which the degree of freedom A of ethylene carbonate represented by the following formula (1) is 30% or less, and a lithium secondary battery containing the non-aqueous electrolyte: Equation (1): A={P free-EC / (P free-EC +P Coordination-EC )}×100 In the above formula 1, A is the degree of freedom of ethylene carbonate, and P free-EC The Raman spectrum of the electrolyte was measured at 893 cm -1 is the integral area of ​​the graph obtained by deconvolution with a Gaussian function based on the peak of P Coordination-EC The Raman spectrum of the electrolyte was measured at 903 cm -1 This is the integral area of ​​the graph obtained by deconvolution with a Gaussian function based on the peak of
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0039950 filed on March 30, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a non-aqueous electrolyte and a lithium secondary battery including the same, and more particularly to a non-aqueous electrolyte capable of suppressing a change in cell volume during operation of the lithium secondary battery, and a lithium secondary battery including the same. [Background technology]

[0003] In recent years, interest in energy storage technology has been growing, and as its application fields expand to mobile phones, video cameras, and laptops, as well as the power sources of electric vehicles, more and more efforts are being made in the research and development of electrochemical devices.

[0004] Among electrochemical elements, interest has been growing in the development of secondary batteries that can be charged and discharged. In particular, lithium secondary batteries, developed in the early 1990s, have attracted attention due to their advantages of high operating voltage and significantly high energy density.

[0005] Lithium secondary batteries are generally manufactured by forming an electrode assembly by interposing a separator between a positive electrode including a positive electrode active material made of a lithium-containing transition metal oxide and a negative electrode including a negative electrode active material capable of storing lithium ions, inserting the electrode assembly into a battery case, injecting a non-aqueous electrolyte that serves as a medium for transferring lithium ions, and then sealing the battery case. The non-aqueous electrolyte is generally composed of a lithium salt and an organic solvent capable of dissolving the lithium salt.

[0006] Carbonate solvents are mainly used as organic solvents for non-aqueous electrolytes, and ethylene carbonate is a solvent that is commonly used to dissociate lithium salts with a high dielectric constant. However, ethylene carbonate is decomposed by reaction with O2 radicals generated at the positive electrode under high voltage and high temperature conditions, generating CO2 gas as a decomposition product. In recent years, as the demand for secondary batteries having high energy density such as batteries for electric vehicles increases, lithium secondary batteries that operate at high voltages have been developed. However, gas generation due to the decomposition of ethylene carbonate during operation of such high voltage lithium secondary batteries can cause serious problems in the safety of the cells. Therefore, there is a need for the development of a non-aqueous electrolyte that can suppress the decomposition of ethylene carbonate, minimize gas generation, and improve the safety of lithium secondary batteries. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made to solve the above-mentioned problems, and aims to provide a nonaqueous electrolyte that generates less CO2 gas and can suppress volume change during cell operation by adjusting the degree of freedom of ethylene carbonate in the electrolyte to satisfy a specific range, and a lithium secondary battery including the same. [Means for solving the problem]

[0008] According to one embodiment, the present invention provides a non-aqueous electrolyte comprising an organic solvent containing ethylene carbonate, a non-solvent, and a lithium salt, wherein the degree of freedom A of the ethylene carbonate represented by the following formula (1) is 30% or less, preferably 10% to 30%, and more preferably 20% to 30%.

[0009] Formula (1): A={P free-EC / (P free-EC +P Coordination-EC )}×100 In the above formula 1, A is the degree of freedom of ethylene carbonate, and P free-ECThe Raman spectrum of the electrolyte was measured at 893 cm -1 is the integral area of ​​the graph obtained by deconvolution with a Gaussian function based on the peak of P Coordination-EC The Raman spectrum of the electrolyte was measured at 903 cm -1 This is the integral area of ​​the graph obtained by deconvolution with a Gaussian function based on the peak of

[0010] In the non-aqueous electrolyte, the volume ratio of the non-solvent to the volume of the ethylene carbonate may be 1-6, preferably 1-5, and more preferably 1-4.

[0011] Specifically, the ethylene carbonate may be contained in an amount of 1 vol% to 10 vol%, preferably 3 vol% to 10 vol%, and more preferably 5 vol% to 10 vol%, based on the total volume of the non-aqueous electrolyte, and the non-solvent may be contained in an amount of 10 vol% to 40 vol%, and preferably 10 vol% to 30 vol%, based on the total volume of the non-aqueous electrolyte.

[0012] The non-solvent may be, for example, one or more selected from the group consisting of fluorobenzene, difluorobenzene, hexafluorobenzene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE), and bis(2,2,2-trifluoroethyl)ether (BTFE). The lithium salt may be contained at a concentration of 1.3M to 2M, preferably 1.3M to 1.8M, and more preferably 1.3M to 1.7M.

[0013] On the other hand, the organic solvent may further include a linear carbonate solvent, and the linear carbonate solvent may be included in an amount of 50 vol% to 85 vol%, preferably 50 vol% to 80 vol%, and more preferably 60 vol% to 80 vol%, based on the total volume of the non-aqueous electrolyte.

[0014] According to another embodiment, the present invention provides a lithium secondary battery comprising the non-aqueous electrolyte according to the present invention described above. Effect of the Invention

[0015] The non-aqueous electrolyte according to the present invention is able to reduce the content of ethylene carbonate in the electrolyte and the amount of free ethylene carbonate that is not coordinated with lithium ions by partially replacing ethylene carbonate with a non-solvent that does not participate in the dissociation of lithium in the electrolyte. Specifically, the non-aqueous electrolyte according to the present invention exhibits an effect of significantly reducing the generation of CO2 gas when the degree of freedom A of ethylene carbonate represented by the formula (1) is 30% or less and the degree of freedom A of ethylene carbonate satisfies the above range.

[0016] If the content of ethylene carbonate in the non-aqueous electrolyte is high, ethylene carbonate is oxidized and decomposed at the positive electrode during charging and discharging, which generates CO2 and thus adversely affects the safety of the battery. Although the CO2 generated by the decomposition of ethylene carbonate can be reduced by reducing the proportion of ethylene carbonate in the organic solvent, the amount of gas generated by the decomposition of linear carbonates such as ethyl methyl carbonate and dimethyl carbonate, which are increased in place of ethylene carbonate, increases the amount of gas generated, such as CH4, and the reduction in the amount of gas generated is negligible.

[0017] Meanwhile, when ethylene carbonate forms a coordinate bond with lithium ions in a non-aqueous electrolyte, the oxidation stability is increased and the oxidative decomposition of ethylene carbonate is suppressed, whereas ethylene carbonate not bonded to lithium ions is oxidatively decomposed at the positive electrode to generate CO2 gas. That is, the amount of gas generated by the decomposition of ethylene carbonate is greatly affected by the content of free ethylene carbonate. When the concentration of the lithium salt is increased, the proportion of free ethylene carbonate can be reduced, but as the concentration of the lithium salt increases, the viscosity of the electrolyte increases, the conductivity decreases, and the life characteristics of the lithium secondary battery decrease.

[0018] Therefore, in the present invention, instead of reducing the content of ethylene carbonate, a non-solvent that does not participate in the dissociation of lithium in the electrolyte is used in combination, thereby making it possible to reduce both the content of ethylene carbonate in the electrolyte and the amount of free ethylene carbonate that is not coordinated with lithium ions without increasing the content of linear carbonate or the concentration of lithium salt, thereby effectively reducing the generation of CO2 gas and minimizing the deterioration of life characteristics.

[0019] On the other hand, since non-solvents generally have lower viscosity characteristics than ethylene carbonate, when a non-solvent is used in combination as in the present invention, the effect of lowering the viscosity of the electrolyte can also be obtained.

[0020] By applying the nonaqueous electrolyte according to the present invention, gas generation and electrolyte depletion during operation of the lithium secondary battery can be effectively prevented, thereby realizing a lithium secondary battery with excellent life characteristics and safety. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a diagram showing a Raman spectrum of the nonaqueous electrolyte of Example 1. [Diagram 2]FIG. 2 is a graph showing the life characteristics of lithium secondary batteries using the nonaqueous electrolytes of Examples 1 to 3 and Comparative Examples 1 to 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] The present invention will now be described in more detail. [Non-aqueous electrolyte] The nonaqueous electrolyte according to the present invention contains (1) an organic solvent containing ethylene carbonate, (2) a non-solvent, and (3) a lithium salt, and the degree of freedom A of the ethylene carbonate represented by the following formula (1) is 30% or less, preferably 10% to 30%, and more preferably 20% to 30%.

[0023] Formula (1): A={P free-EC / (P free-EC +P Coordination-EC )}×100 In the formula (1), A is the degree of freedom of ethylene carbonate, and P free-EC The Raman spectrum of the electrolyte was measured at 893 cm -1 is the integral area of ​​the graph obtained by deconvolution with a Gaussian function based on the peak of P Coordination-EC The Raman spectrum of the electrolyte was measured at 903 cm -1 This is the integral area of ​​the graph obtained by deconvolution with a Gaussian function based on the peak of

[0024] The degree of freedom (A) of ethylene carbonate is a value indicating the proportion of free ethylene carbonate that is not coordinately bonded to lithium ions to the total ethylene carbonate in the electrolyte. -1 Peak P appears near free-EC is a peak due to free ethylene carbonate that is not bound to lithium ions, and 903 cm -1 Peak P appears near Coordination-ECis a peak that appears due to ethylene carbonate coordinated with lithium ions. Meanwhile, the integrated area of ​​each peak corresponds to the content of the component that shows the peak. Therefore, P in formula (1) free-EC / (P free-EC +P Coordination-EC ) is a value corresponding to the proportion of free ethylene carbonate in the total ethylene carbonate present in the electrolyte.

[0025] On the other hand, when ethylene carbonate forms a coordinate bond with lithium ions, the oxidation stability is increased, and the oxidative decomposition of ethylene carbonate is suppressed, and ethylene carbonate not bonded to lithium ions is oxidatively decomposed at the positive electrode to generate CO2 gas. That is, the amount of gas generated by the decomposition of ethylene carbonate is greatly affected by the proportion of free ethylene carbonate. According to the research of the present inventors, when the proportion of free ethylene carbonate in the total ethylene carbonate in the electrolyte is 30% or less, that is, when the degree of freedom A of ethylene carbonate represented by formula (1) is 30% or less, it has been revealed that the amount of CO2 gas generated is significantly reduced and the deterioration of life characteristics is minimized. When the degree of freedom A of ethylene carbonate represented by formula (1) exceeds 30%, the effect of reducing CO2 is reduced, volume change may occur during cell operation, and life characteristics may be significantly reduced.

[0026] Preferably, the degree of freedom A of ethylene carbonate represented by the formula (1) may be 10% to 30%, more preferably 20% to 30%. The smaller the degree of freedom A of ethylene carbonate, the more the decomposition of ethylene carbonate is suppressed, which is advantageous for reducing the amount of gas generated, but when the content of ethylene carbonate is reduced or the content of lithium salt is increased in order to reduce the degree of freedom A, problems such as insufficient formation of the SEI film of the negative electrode, increased viscosity of the electrolyte, and reduced ion conductivity may occur, resulting in reduced cell performance.

[0027] The degree of freedom A of ethylene carbonate represented by the above formula (1) can be adjusted by adjusting the composition of the solvent in the nonaqueous electrolyte and the concentration of the lithium salt. Each of the components of the nonaqueous electrolyte according to the present invention will now be described in more detail.

[0028] (1) Organic Solvent In the present invention, the organic solvent includes ethylene carbonate. Ethylene carbonate has a high dielectric constant and can easily dissociate lithium salts in an electrolyte solution, so that when ethylene carbonate is used as an organic solvent, it is possible to realize excellent lithium mobility and excellent electrochemical performance.

[0029] In the present invention, the ethylene carbonate may be contained in an amount of 10% by volume or less, preferably 1% by volume to 10% by volume, more preferably 3% by volume to 10% by volume, and even more preferably 5% by volume to 10% by volume, based on the total volume of the non-aqueous electrolyte. When the content of ethylene carbonate satisfies the above range, it is easy to adjust the value A in formula (1) to 30% or less, and a non-aqueous electrolyte having high lithium ion conductivity and low gas generation can be produced. Specifically, if the content of ethylene carbonate is too low, the lithium ion conductivity may decrease, and the electrochemical properties may decrease, and if the content of ethylene carbonate is too high, the proportion of free ethylene carbonate may increase, and the gas generation may increase.

[0030] Meanwhile, the organic solvent may further include a linear carbonate-based solvent in addition to ethylene carbonate. The linear carbonate-based solvent is an organic solvent having low viscosity and low dielectric constant, and may be, for example, at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate.

[0031] The linear carbonate solvent may be contained in an amount of 50% by volume to 85% by volume, preferably 50% by volume to 80% by volume, more preferably 60% by volume to 80% by volume, based on the total volume of the non-aqueous electrolyte. When the content of the linear carbonate solvent satisfies the above range, the viscosity of the non-aqueous electrolyte can be appropriately maintained, and the effect of reducing gas generation is excellent. If the content of the linear carbonate solvent is too low, the viscosity of the non-aqueous electrolyte may increase and the ion conductivity may decrease, and if the content of the linear carbonate solvent is too high, the linear carbonate solvent may be decomposed during operation of the battery, causing excessive generation of gas such as CH4, and the effect of suppressing gas generation may decrease.

[0032] On the other hand, although not essential, the organic solvent may further contain a cyclic carbonate solvent other than ethylene carbonate, a linear ester solvent, or the like, if necessary.

[0033] As the cyclic carbonate solvent other than ethylene carbonate, for example, at least one selected from the group consisting of propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate may be used, and as the linear ester solvent, for example, at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate may be used.

[0034] (2) Non-solvent The non-solvent is a solvent that has low solubility for lithium salt and does not participate in the dissociation of lithium salt. In the present invention, instead of reducing the content of ethylene carbonate, a non-solvent that does not participate in the dissociation of lithium in the electrolyte is used in combination, thereby making it possible to reduce the amount of free ethylene carbonate in the electrolyte without increasing the concentration of the lithium salt. Even if the content of ethylene carbonate is reduced, if the content of a solvent such as a linear carbonate that forms a coordinate bond with lithium ions increases, the bonds between the increased linear carbonate and lithium ions increase, so there is a limit to the increase in the ratio of ethylene carbonate that forms a coordinate bond with lithium ions. Therefore, the reduction in the ratio of free ethylene carbonate in the total ethylene carbonate is limited. However, since the non-solvent does not bond with lithium ions and does not affect the degree of dissociation of ethylene carbonate, when a non-solvent is added in an amount corresponding to the reduction in the content of ethylene carbonate, the ratio of free ethylene carbonate in the total ethylene carbonate can be effectively reduced.

[0035] As the non-solvent, for example, one or more selected from the group consisting of fluorobenzene, difluorobenzene, hexafluorobenzene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE), and bis(2,2,2-trifluoroethyl)ether (BTFE) may be used, and among them, fluorobenzene is particularly preferred. Since fluorobenzene has a lower viscosity characteristic than ethylene carbonate, when fluorobenzene is used as the non-solvent, it is possible to obtain an effect of lowering the viscosity of the electrolyte, and there is no oxidation / reduction reaction at the driving potential of the secondary battery, which is 2.5 to 4.3 V, and the electrolyte is electrochemically stable.

[0036] Meanwhile, the non-solvent may be included in an amount of 10% by volume to 40% by volume, preferably 10% by volume to 30% by volume, based on the total volume of the non-aqueous electrolyte. When the content of the non-solvent satisfies the above range, the amount of CO2 generated is significantly reduced, and an excellent viscosity reducing effect of the non-aqueous electrolyte is exhibited.

[0037] Meanwhile, in the non-aqueous electrolyte according to the present invention, the volume ratio of the non-solvent to the volume of the ethylene carbonate may be 1 to 6, preferably 1 to 5, and more preferably 1 to 4. When the volume ratio of the non-solvent to the ethylene carbonate satisfies the above range, an excellent effect of reducing the amount of gas generation and an excellent effect of reducing the viscosity of the non-aqueous electrolyte are exhibited. When the non-solvent is contained in a volume smaller than that of the ethylene carbonate, the effect of suppressing gas generation is insignificant, and when the volume of the non-solvent to the ethylene carbonate is excessively high, the lithium ion conductivity decreases, and the electrochemical properties may deteriorate.

[0038] (3) Lithium salt As the lithium salt used in the present invention, various lithium salts commonly used in electrolytes for lithium secondary batteries can be used without limitation. For example, the lithium salt has a cation of Li + The anion is F. - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , AlO4 - , AlCl4 - , PF6 - , SbF6 - , AsF6 - , B 10 Cl 10 - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 -, (CF3)5PF - , (CF3)6P - , CF3SO3 - , C4F9SO3 - , CF3CF2SO3 - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , CH3SO3 - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - , and (CF3CF2SO2)2N - The present invention may include at least one selected from the group consisting of:

[0039] Specifically, the lithium salts include LiCl, LiBr, LiI, LiBF4, LiClO4, LiAlO4, LiAlCl4, LiPF6, LiSbF6, LiAsF6, LiB 10 Cl 10 , LiBOB (LiB (C2O4)2), LiCF3SO3, LiFSI (LiN (SO2F)2), LiCH3SO3, LiCF3CO2, LiCH3CO2, and LiBETI (LiN (SO2CF2CF3)2). Specifically, the lithium salt may include a single substance or a mixture of two or more substances selected from the group consisting of LiBF4, LiClO4, LiPF6, LiBOB (LiB (C2O4)2), LiCF3SO3, LiTFSI (LiN (SO2CF3)2), LiFSI (LiN (SO2F)2), and LiBETI (LiN (SO2CF2CF3)2).

[0040] The lithium salt may be contained in the non-aqueous electrolyte at a concentration of 1.3 M to 2 M, preferably 1.3 M to 1.8 M, and more preferably 1.3 M to 1.7 M. When the concentration of the lithium salt is less than 1.3 M, the amount of lithium ions capable of forming coordinate bonds with ethylene carbonate is small, making it difficult to reduce the proportion of free ethylene carbonate to a desired level, limiting the reduction in the amount of CO2 generated, and decreasing the lithium mobility in the electrolyte, which may result in degraded life characteristics.

[0041] On the other hand, since the nonaqueous electrolyte of the present invention contains a nonsolvent with a low degree of dissociation of lithium salt, when the concentration of lithium salt exceeds 2 M, the lithium salt does not dissociate completely, and the viscosity of the electrolyte increases and the ionic conductivity may decrease.

[0042] (4) Other ingredients Meanwhile, the non-aqueous electrolyte according to the present invention may further contain, although not essential, an additive in addition to the above components in order to further improve the physical properties of the secondary battery.

[0043] Examples of such additives include at least one selected from the group consisting of cyclic carbonate compounds, halogen-substituted carbonate compounds, sultone compounds, sulfate compounds, phosphate compounds, borate compounds, amine compounds, silane compounds, and lithium salt compounds.

[0044] The cyclic carbonate compound may be, for example, vinylene carbonate (VC) or vinyl ethylene carbonate (VEC). The halogen-substituted carbonate compound may be, for example, fluoroethylene carbonate (FEC).

[0045] The sultone compound may be, for example, 1,3-propane sultone, 1,3-propene sultone, and the like. The sulfate compound may be, for example, ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyl trimethylene sulfate (MTMS).

[0046] The phosphate-based compound may be, for example, one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tetramethyltrimethylsilylphosphate, trimethylsilylphosphite, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphite.

[0047] The borate-based compound may be, for example, tetraphenylborate, lithium oxalyldifluoroborate (LiODFB), and the like. The amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane.

[0048] The lithium salt compound is a compound different from the lithium salt contained in the nonaqueous electrolyte, and may be one or more compounds selected from the group consisting of LiPO2F2, LiODFB, LiBOB (lithium bis(oxalato)borate (LiB(C2O4)2), and LiBF4. On the other hand, the additives may be used alone or in combination of two or more kinds.

[0049] The total amount of the additives may be 0.1 wt % to 20 wt %, preferably 0.1 wt % to 15 wt %, based on the total weight of the electrolyte. When the additives are contained within the above range, a stable coating is formed on the electrode, and ignition during overcharge can be suppressed, while side reactions can be prevented from occurring during the initial activation process of the secondary battery, or the additives can be prevented from remaining or depositing.

[0050] [Lithium secondary battery] Next, the lithium secondary battery according to the present invention will be described. The lithium secondary battery according to the present invention contains the non-aqueous electrolyte according to the present invention described above. More specifically, the lithium secondary battery according to the present invention includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte. At this time, the non-aqueous electrolyte is the non-aqueous electrolyte according to the present invention described above. Since the non-aqueous electrolyte has been described above, the description thereof will be omitted, and other components will be described below.

[0051] Positive electrode The positive electrode may include a positive electrode active material layer containing a positive electrode active material, and if necessary, the positive electrode active material layer may further contain a conductive material and / or a binder.

[0052] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium, and various positive electrode active materials used in the art, for example, lithium-manganese-based oxides (e.g., LiMnO2, LiMn2O4, etc.), lithium-cobalt-based oxides (e.g., LiCoO2, etc.), lithium-nickel-based oxides (e.g., LiNiO2, etc.), lithium-nickel-manganese-based oxides (e.g., LiNi 1-Y Mn Y O2(0 < Y < 1), LiMn 2-z Ni z O4(0 < Z < 2), lithium-nickel-cobalt-based oxides (e.g., LiNi 1-Y1 Co Y1 O2(0 < Y1 < 1), lithium-manganese-cobalt-based oxides (e.g., LiCo 1-Y2 Mn Y2 O2(0 < Y2 < 1), LiMn 2-z1 Co z1 O4(0 < Z1 < 2), lithium-nickel-manganese-cobalt-based oxides (e.g., Li(Ni p1 Co q1 Mn r1)O2(0 < p1 < 1, 0 < q1 < 1, 0 < r1 < 1, p1 + q1 + r1 = 1), or Li(Ni p2 Co q2 Mn r2 )O4(0 < p2 < 2, 0 < q2 < 2, 0 < r2 < 2, p2 + q2 + r2 = 2), or lithium-nickel-cobalt-transition metal (M) oxide (e.g., Li(Ni p3 Co q3 Mn r3 M s3 )O2 (M is selected from the group consisting of Al, Fe, V, Cr, Ti, Ta, Mg, and Mo, and p3, q3, r3, and s3 are atomic fractions of independent elements, where 0 < p3 < 1, 0 < q3 < 1, 0 < r3 < 1, 0 < s3 < 1, and p3 + q3 + r3 + s3 = 1)) may be used.

[0053] Preferably, the positive electrode active material may contain at least one or more of the lithium manganese-based oxide represented by the following [Chemical Formula 1] and the lithium nickel-based oxide represented by [Chemical Formula 2].

[0054] [Chemical Formula 1] Li 1+x [Ni a Co b Mn c M 1 d ) 1-x O 2-y

[0055] In the above Chemical Formula 1, 0.05 ≤ x ≤ 1, 0 ≤ a ≤ 0.5, 0 ≤ b ≤ 0.1, 0.5 ≤ c ≤ 1.0, 0 ≤ d ≤ 0.2, -1.0 ≤ y ≤ 1.0. M 1 may be at least one or more selected from the group consisting of metal ions Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0056] [Chemical Formula 2] Li 1+x1 [Ni a1 Co b1 Mn c1 M 2 d1]O2

[0057] In the above formula 2, -0.2≦x1≦0.2, 0.8≦a1<1, 0 <b1<0.2、0<c1<0.2、0≦d1≦0.2である。M 2 may be at least one selected from the group consisting of Al, B, Co, W, Mg, V, Ti, Zn, Ga, In, Ru, Nb, Sn, Sr, and Zr.

[0058] A secondary battery using the lithium manganese oxide represented by [Chemical Formula 1] undergoes an activation process at a high voltage of 4.6 V or more, during which ethylene carbonate is oxidized and decomposed at the positive electrode, resulting in the generation of excessive CO2. In addition, the lithium nickel oxide represented by Chemical Formula 2 contains a high content of nickel, making it structurally unstable. When the battery is driven at high temperature or high voltage, however, the nonaqueous electrolyte of the present invention has a low ratio of free ethylene carbonate oxidized and decomposed at the positive electrode, resulting in the generation of excessive CO2. However, when the nonaqueous electrolyte of the present invention is used together with the positive electrode active material represented by [Chemical Formula 1] and / or [Chemical Formula 2], the generation of CO2 can be effectively reduced. The positive electrode active material may be contained in an amount of 80% by weight to 99.9% by weight, preferably 85% by weight to 99% by weight, based on the total weight of the positive electrode active material layer.

[0059] Next, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1% by weight to 10% by weight, preferably 0.1% by weight to 5% by weight, based on the total weight of the positive electrode active material layer.

[0060] Next, the binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples of the binder include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1% by weight to 15% by weight, preferably 0.1% by weight to 10% by weight, based on the total weight of the positive electrode active material layer.

[0061] The positive electrode of the present invention as described above may be manufactured by a method for manufacturing a positive electrode well known in the art. For example, the positive electrode may be manufactured by a method of coating a positive electrode current collector with a positive electrode slurry prepared by dissolving or dispersing a positive electrode active material, a binder, and / or a conductive material in a solvent, followed by drying and rolling, or by a method of casting the positive electrode slurry on a separate support, peeling off the support, and laminating the resulting film on the positive electrode current collector.

[0062] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0063] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to a level that allows the positive electrode mixture to have an appropriate viscosity in consideration of the coating thickness of the positive electrode mixture, production yield, workability, etc.

[0064] negative electrode Next, the negative electrode will be described. The negative electrode according to the present invention includes a negative electrode active material layer containing a negative electrode active material, and the negative electrode active material layer may further include a conductive material and / or a binder, as necessary.

[0065] As the negative electrode active material, various negative electrode active materials used in the art, for example, carbon-based negative electrode active materials, silicon-based negative electrode active materials, metal alloys, etc. may be used. As the carbon-based negative electrode active material, various carbon-based negative electrode active materials used in the art, for example, graphite-based materials such as natural graphite, artificial graphite, and Kish graphite; pyrolytic carbon, mesophase pitch-based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature calcined carbon such as petroleum or coal tar pitch-derived cokes, soft carbon, hard carbon, etc. may be used. The shape of the carbon-based negative electrode active material is not particularly limited, and substances of various shapes such as amorphous, plate-like, flaky, spherical, or fibrous may be used.

[0066] The silicon-based negative electrode active material may contain one or more selected from the group consisting of metallic silicon (Si), silicon oxide (SiOx, where 0 < x < 2), silicon carbide (SiC), and Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, group 13 elements, group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si). As the element Y, it may be selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0067] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material is in the above range, excellent capacity characteristics and electrochemical characteristics can be obtained.

[0068] Next, the conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, graphite such as natural graphite or artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives may be used.

[0069] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0070] The negative electrode may be manufactured by a method for manufacturing a negative electrode well known in the art. For example, the negative electrode may be manufactured by applying a negative electrode slurry, which is prepared by dissolving or dispersing a negative electrode active material and, optionally, a binder and a conductive material in a solvent, onto a negative electrode current collector, followed by rolling and drying, or by casting the negative electrode slurry onto another support, peeling off the support, and laminating the resulting film onto the negative electrode current collector.

[0071] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to strengthen the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0072] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity for the negative electrode slurry in consideration of the coating thickness of the negative electrode composite, production yield, workability, etc.

[0073] Separator Next, the separator will be described. The separator is interposed between the negative electrode and the positive electrode, separates the positive electrode from the negative electrode, and provides a path for lithium ion migration. Any separator that is normally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion migration in the electrolyte and has excellent electrolyte humidification ability.

[0074] Specifically, the separator may be a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof. Also, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, or the like, may be used. Also, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymeric substance may be used, and may be selectively used as a single-layer structure or a multi-layer structure.

[0075] The lithium secondary battery according to the present invention as described above can be effectively used in portable devices such as mobile phones, notebook computers, and digital cameras, as well as in the field of electric vehicles. According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0076] The battery module or battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0077] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0078] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for small devices, but also preferably as a unit battery in a medium- to large-sized battery module including a plurality of battery cells.

[0079] <Example> The present invention will now be described in more detail with reference to specific examples. Example 1 Ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC): fluorobenzene (FB) were mixed in a volume ratio of 10:5:75:10, and LiPF6 was dissolved therein to a concentration of 1.4 M to produce a non-aqueous electrolyte.

[0080] Example 2 Ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC): fluorobenzene (FB) were mixed in a volume ratio of 5:5:75:15, and LiPF6 was dissolved therein to a concentration of 1.4 M to produce a non-aqueous electrolyte.

[0081] Example 3 Ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC): fluorobenzene (FB) were mixed in a volume ratio of 10:5:75:10, and LiPF6 was dissolved therein to a concentration of 1.6 M to produce a non-aqueous electrolyte.

[0082] Comparative Example 1 Ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) were mixed in a volume ratio of 20:5:75, and LiPF6 was dissolved therein to a concentration of 1.4 M to produce a non-aqueous electrolyte.

[0083] Comparative Example 2 Ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC): fluorobenzene (FB) were mixed in a volume ratio of 15:5:75:5, and LiPF6 was dissolved therein to a concentration of 1.4 M to produce a non-aqueous electrolyte.

[0084] Comparative Example 3 Ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) were mixed in a volume ratio of 10:5:85, and LiPF6 was dissolved therein to a concentration of 1.4 M to produce a non-aqueous electrolyte.

[0085] Comparative Example 4 Ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) were mixed in a volume ratio of 5:95, and LiPF6 was dissolved therein to a concentration of 1.4 M to produce a non-aqueous electrolyte.

[0086] Comparative Example 5 Ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC): fluorobenzene (FB) were mixed in a volume ratio of 10:5:75:10, and LiPF6 was dissolved therein to a concentration of 1.2 M to produce a non-aqueous electrolyte.

[0087] [Table 1]

[0088] [Experimental Example 1] The Raman spectra of the nonaqueous electrolytes produced in Examples 1 to 3 and Comparative Examples 1 to 5 were measured using a Raman spectrometer (ThermoFisher, model name: DXR3Xi), and the degree of freedom A of ethylene carbonate according to formula (1) was calculated using the results. The measurement results are shown in Table 2 below. Also, FIG. 1 shows the Raman spectrum of the nonaqueous electrolyte of Example 1.

[0089] [Experimental Example 2] The viscosity (unit: cps) of the non-aqueous electrolytes prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was measured at 25° C. and 250 rpm using a viscometer (Brookfield Corporation, model name: DV-3 ULTRA), and the viscosity increase rate was calculated based on the viscosity of the non-aqueous electrolyte of Comparative Example 1, and is shown in the following Table 2. The viscosity increase rate was calculated using the following formula (2). Equation (2): Viscosity increase rate (%)={(measured viscosity of nonaqueous electrolyte−viscosity of nonaqueous electrolyte of Comparative Example 1) / viscosity of nonaqueous electrolyte of Comparative Example 1}×100

[0090] <Manufacturing lithium secondary batteries> (Production of positive electrodes) LiNi as the positive electrode active material 0.8 Co 0.1 Mn 0.1 A positive electrode slurry was prepared by adding O2, carbon black as a conductive material, and polyvinylidene fluoride (PVDF) as a binder in a weight ratio of 98:1:1 to N-methyl-2-pyrrolidone (NMP) as a solvent. The positive electrode slurry was applied to a positive electrode current collector (aluminum thin film), dried, and roll pressed to prepare a positive electrode.

[0091] (Production of negative electrodes) Anode active material graphite, binder PVDF, and conductive material carbon black were mixed in a weight ratio of 96:1:3 with NMP as a solvent to prepare anode slurry. The anode slurry was applied to an anode current collector (Cu thin film), dried, and roll pressed to prepare anode.

[0092] (Secondary battery manufacturing) The positive and negative electrodes prepared as described above were sequentially laminated together with a polyethylene porous film to prepare an electrode assembly in a conventional manner, which was then placed in a pouch-type secondary battery case, and the non-aqueous electrolyte prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was injected to prepare a lithium secondary battery.

[0093] [Experimental Example 3] Each lithium secondary battery manufactured above was fully charged and stored at 72°C for 30 days, after which a pinhole was opened in the battery case, and the gas generated for 1 minute was collected under negative pressure, and the amount of CO2 generated (unit: μL) and the amount of CH4 generated (unit: μL) were measured by chromatography. Next, the increase rate of the amount of gas generated was calculated based on Comparative Example 1 using formula (3), and shown in Table 2 below. Equation (3): Increase rate of gas generation amount (%)={(measured gas generation amount−gas generation amount in Comparative Example 1) / gas generation amount in Comparative Example 1}×100

[0094] [Table 2]

[0095] From Table 2, it can be seen that the amount of CO2 gas generated from the nonaqueous electrolytes of Examples 1 to 3, which contain a nonsolvent and have a degree of freedom A of ethylene carbonate of 30% or less, is less than that of the nonaqueous electrolytes of Comparative Examples 1 to 5.

[0096] In the case of the nonaqueous electrolyte of Comparative Example 3, in which a nonsolvent was not used, the content of linear carbonate was increased, and the degree of freedom A of ethylene carbonate was adjusted to 30% or less, the amount of CO2 reduction was smaller than those of the nonaqueous electrolytes of Examples 1 to 3, and the amount of CH4 gas generation increased significantly.

[0097] [Experimental Example 4] The lithium secondary batteries manufactured by injecting the non-aqueous electrolytes of Examples 1 to 3 and Comparative Examples 1 to 5 were each charged at 25° C. under CC / CV and 1C conditions up to 4.2V (0.05C cut off). Then, the batteries were discharged under CC and 1C conditions up to 3V. The above charge and discharge behavior was counted as one cycle, and the capacity retention rate was measured while repeating such a cycle 120 times. The measurement results are shown in FIG. 2.

[0098] 2, it can be seen that the secondary batteries using the nonaqueous electrolytes of Examples 1 to 3 had comparable life characteristics, despite the fact that the amount of gas generated was significantly reduced compared to the secondary batteries using the nonaqueous electrolytes of Comparative Examples 1 and 2. In contrast, it was clear that the secondary batteries using the nonaqueous electrolytes of Comparative Examples 3 to 5 had deteriorated life characteristics compared to the secondary batteries of Examples 1 to 3 and Comparative Examples 1 and 2.

Claims

1. An organic solvent including ethylene carbonate, a non-solvent, and a non-aqueous electrolyte including a lithium salt, A non-aqueous electrolyte, in which the degree of freedom A of ethylene carbonate represented by the following formula (1) is 30% or less: Formula (1): A = {P free-EC / (P free-EC +P Coordination-EC )}×100 In the above formula 1, A is the degree of freedom of ethylene carbonate, P free-EC The Raman spectrum of the non-aqueous electrolyte was measured at 893 cm -1 is the integral area of ​​the graph obtained by deconvolution with a Gaussian function based on the peak of P Coordination-EC The Raman spectrum of the non-aqueous electrolyte was measured at 903 cm -1 This is the integral area of ​​the graph obtained by deconvolution with a Gaussian function using the peak of

2. 2. The nonaqueous electrolyte according to claim 1, wherein the degree of freedom A of the ethylene carbonate represented by the formula (1) is 20% to 30%.

3. 2. The non-aqueous electrolyte according to claim 1, wherein a volume ratio of the non-solvent to the volume of the ethylene carbonate is 1 to 6.

4. 2. The non-aqueous electrolyte according to claim 1, wherein the ethylene carbonate is contained in an amount of 1 vol. % to 10 vol. % based on the total volume of the non-aqueous electrolyte.

5. 2. The non-aqueous electrolyte according to claim 1, wherein the non-solvent is contained in an amount of 10% by volume to 40% by volume based on the total volume of the non-aqueous electrolyte.

6. The non-solvent is at least one selected from the group consisting of fluorobenzene, difluorobenzene, hexafluorobenzene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE), and bis(2,2,2-trifluoroethyl)ether (BTFE). The non-aqueous electrolyte according to claim 1.

7. The non-aqueous electrolyte according to claim 1 , wherein the lithium salt is contained at a concentration of 1.3 M to 2 M.

8. The non-aqueous electrolyte according to claim 1 , wherein the organic solvent further comprises a linear carbonate solvent.

9. The non-aqueous electrolyte according to claim 8 , wherein the linear carbonate solvent is contained in an amount of 50% by volume to 85% by volume based on the total volume of the non-aqueous electrolyte.

10. A lithium secondary battery comprising the non-aqueous electrolyte according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Lithium cell having efficient performance

    JP2005135895A